Roles of Glutamate Synthase, gltBD, and gltF in Nitrogen Metabolism of Escherichia coli and Klebsiella aerogenes - Goss, Thomas J. (American Society for Microbiology, 2001)
Mutants of Escherichia coli and Klebsiella aerogenes that are deficient in glutamate synthase (glutamate-oxoglutarate amidotransferase [GOGAT]) activity have difficulty growing with nitrogen sources other than ammonia. Two models have been proposed to account for this inability to grow. One model postulated an imbalance between glutamine synthesis and glutamine degradation that led to a repression of the Ntr system and the subsequent failure to activate transcription of genes required for the use of alternative nitrogen sources. The other model postulated that mutations in gltB or gltD (which encode the subunits of GOGAT) were polar on a downstream gene, gltF, which is necessary for proper activation of gene expression by the Ntr system. The data reported here show that the gltF model is incorrect for three reasons: first, a nonpolar gltB and a polar gltD mutation of K. aerogenes both show the same phenotype; second, K. aerogenes and several other enteric bacteria lack a gene homologous to gltF; and third, mutants of E. coli whose gltF gene has been deleted show no defect in nitrogen metabolism. The argument that accumulated glutamine represses the Ntr system in gltB or gltD mutants is also incorrect, because these mutants can derepress the Ntr system normally so long as sufficient glutamate is supplied. Thus, we conclude that gltB or gltD mutants grow slowly on many poor nitrogen sources because they are starved for glutamate. Much of the glutamate formed by catabolism of alternative nitrogen sources is converted to glutamine, which cannot be efficiently converted to glutamate in the absence of GOGAT activity. Finally, GOGAT-deficient E. coli cells growing with glutamine as the sole nitrogen source increase their synthesis of the other glutamate-forming enzyme, glutamate dehydrogenase, severalfold, but this is still insufficient to allow rapid growth under these conditions.